The Relationship Between Language and Consciousness in Wilhelm Von Humboldt’s Linguistic Philosophy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Wilhelm von Humboldt's linguistic philosophy posits a profound interconnection between language and human consciousness, viewing language not merely as a communicative tool but as an active force (energeia) that shapes thought and worldview. This article explores this relationship through an analysis of Humboldt's key works, particularly On the Diversity of Human Language Construction and Its Influence on the Mental Development of the Human Species. Drawing on historical and philosophical contexts, it examines how language structures consciousness, influences cultural diversity, and serves as the medium for conceptual formation. The discussion highlights Humboldt's departure from semiotic traditions and his emphasis on linguistic relativity, with implications for modern linguistics and cognitive science. Findings underscore language's role in human mental development, bridging individual cognition and collective cultural experience.